The Effects of Percutaneous Endoscopic Gastrostomy on Quality of Life in Patients With Dementia - Suzuki, Yutaka (Gastroenterology Res, 2012)
BACKGROUND: To examine the effects of percutaneous endoscopic gastrostomy (PEG) on quality of life (QOL) in patients with dementia. METHODS: We retrospectively included 53 Japanese community and tertiary hospitals to investigate the relationship between the newly developed PEG and consecutive dementia patients with swallowing difficulty between Jan 1st 2006 and Dec 31st 2008. We set improvements in 1) the level of independent living, 2) pneumonia, 3) peroral intake as outcome measures of QOL and explored the factors associated with these improvements. RESULTS: Till October 31st 2010, 1,353 patients with Alzheimer’s dementia (33.1%), vascular dementia (61.7%), dementia with Lewy body disease (2.0%), Pick disease (0.6%) and others were followed-up for a median of 847 days (mean 805 ± 542 days). A total of 509 deaths were observed (mortality 59%) in full-followed patients. After multivariate adjustments, improvement in the level of independent living was observed in milder dementia, or those who can live independently with someone, compared with advanced dementia, characterized by those who need care by someone: Odds Ratio (OR), 3.90, 95% confidence interval (95%CI), 1.59 - 9.39, P = 0.003. Similarly, improvement of peroral intake was noticed in milder dementia: OR, 2.69, 95%CI, 1.17 - 6.17, P = 0.02. Such significant associations were not observed in improvement of pneumonia. CONCLUSIONS: These results suggest that improvement of QOL after PEG insertion may be expected more in milder dementia than in advanced dementia.